Why not travel to Malaysia? variations in inbound tourists perceptions toward halal-friendly destination attributes - Azali, Mohamed; Kamal Basha, Norazlyn; Chang, Yee-Shan; Lim, Xin-Jean; Cheah, Jun-Hwa (SAGE Publications, 2021)
The importance of halal tourism has prompted countries and business operators to place more emphasis on this lucrative sector. The purpose of this study is to investigate the effects of halal-friendly destination attributes on inbound tourists’ behavioral intention in the context of Malaysia. Furthermore, a comparative analysis was conducted to investigate the similarities and differences between Chinese and Indonesian Muslim tourists. A total of 666 observations were collected using surveys and the data sets were analyzed via partial least squares structural equation modeling. The empirical results show that both countries have indicated variations in terms of preferences for social environment, services, and facilities. We contribute to the knowledge on the constitutive attributes of the halal-friendly destination, while providing theoretical explanations for the differences among Muslim tourists in the Asian markets. Finally, directions for future research are proposed.